Kura Clover Living Mulch for Furrow‐Irrigated Corn in the Intermountain West. (1st July 2014) - Pearson, Calvin H.; Brummer, Joe E.; Beahm, Andrew T.; Hansen, Neil C.
Abstract : Kura clover ( Trifolium ambiguum M. Bieb.) living mulches have been used successfully to produce corn ( Zea mays L.) in the upper Midwest. A study was conducted at Fruita, CO (39.1500° N, 108.7167° W), to evaluate corn production in a kura clover living mulch system under furrow irrigation. Living mulch treatments were: (i) no‐till, (ii) no‐till with a pre‐plant herbicide application, and (iii) strip‐tillage. Nitrogen fertilization rates of 0, 84, and 168 kg N ha −1 were applied to living mulch plots and 0, 168, and 336 kg N ha −1 were applied to conventional corn plots. Grain yield was responsive to N rate with highest yields in kura clover living mulch plots occurring at 168 kg N ha −1 (10.1 and 10.8 Mg ha −1 in 2007 and 2008, respectively). The strip‐till treatment performed best in 2007, yielding 11.7 Mg ha −1 at 168 kg N ha −1, but did not differ from the no‐till with pre‐plant herbicide in 2008. Averaged across tillage treatments, kura clover biomass was highest (991 kg ha −1 ) when no N was applied and the difference in kura clover biomass was not significant between the 84 and 168 kg ha −1 N rates. There was no difference in kura clover production among suppression treatments (averaging 726 kg ha −1 ). Strip‐tillage at a 168 kg N ha −1 rate is a promising option for producing grain corn in a kura clover living mulch cropping system under furrow irrigation in the Intermountain West.